Temporal characteristics of hyolaryngeal structural movements in normal swallowing. (16th March 2015) - Nam, Hyung Seok; Oh, Byung‐Mo; Han, Tai Ryoon
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the relationship between movements of hyolaryngeal structures and fluid bolus transition in normal swallowing using automatized kinematic analysis of the videofluoroscopic swallowing study (VFSS). Study Design A prospective, descriptive study. Methods Seventy‐five healthy volunteers underwent VFSS with 2 mL of diluted barium. The timing and sequence of structural movements were measured for laryngeal elevation (LE), hyoid excursion (HE), epiglottic rotation (ER), and fluid bolus transition. Results The rapid movement of LE (reference time point) was initiated simultaneously with the fluid bolus head passing the mandibular angle (−0.05 s, P = .07), followed by rapid onset of HE with significant temporal difference (P < .001). After the hyoid onset, onset of ER (0.17 s, P < .001), entrance of the bolus through upper esophageal sphincter (0.33 s, P < .001), maximal point of LE (0.52 s, P < .001), HE (0.53 s, P = .344), and maximal point of ER (0.64 s, P < .001) followed sequentially. For subgroup analysis, we classified 50 subjects without premature bolus loss (PBL) or pharyngeal triggering delay (PTD) into the "early group, " and 24 subjects with PBL or PTD for <1 s into the "late group." In both groups, the sequence of the structural movements did not change. The early group showed significant correlation between the fluid transition and structural movements; both LE and HE were initiated when the bolus passed the mandibular angle, and the ER was initiated when the bolus reached the vallecula. Conclusions We demonstrated a characteristic pattern of hyolaryngeal structural movements in normal swallowing. The results may serve as a basis for classifying and analyzing aspiration patterns in patients with dysphagia. Level of Evidence NA Laryngoscope, 125:2129–2133, 2015